Cervical cord functional MRI changes in relapse-onset MS patients. Issue 4 (3rd December 2009) - Valsasina, P; Agosta, F; Absinta, M; Sala, S; Caputo, D; Filippi, M
Abstract : Objective: To investigate whether (1) the tactile-associated cord functional MRI (fMRI) changes vary in the different clinical stages of relapse-onset multiple sclerosis (MS), and (2) the pattern of cord fMRI changes relates to severity of MS clinical disability. Methods: Cervical cord fMRI was acquired from 49 MS patients (30 relapsing-remitting (RR), 19 secondary progressive (SP)), and 19 controls, during a tactile stimulation of the right hand. Task-related cord mean signal change and occurrence of fMRI activity at each cord quadrant and level were measured. MRI quantities were compared between groups using an univariate analysis. Between-group differences in topographical distribution of fMRI activity were evaluated using random-effect logistic regression models. Results: Compared with controls, both RRMS (p=0.05) and secondary progressive multiple sclerosis (p=0.02) patients showed a higher cord fMRI activity, whereas no difference was found between patient groups. Severely disabled patients (26/49) showed a cord overactivation relative to controls (p=0.004) and patients with mild disability (p=0.04). Both controls and MS patients showed a functional lateralisation of cord activity, which was predominant in the cord side ipsilateral to the stimulus, and a more frequent activation of the posterior than of the anterior cord quadrants. Discussion: This study shows that tactile-associated cervical cord fMRI activity is increased in relapse-onset MS patients. Such an overactivation is more prominent in patients with more severe locomotor disability. This suggests that an abnormality of cord functional properties may be among the factors associated with the clinical status of MS patients.